2015
DOI: 10.1063/1.4913515
|View full text |Cite
|
Sign up to set email alerts
|

Electron dynamics upon ionization: Control of the timescale through chemical substitution and effect of nuclear motion

Abstract: Articles you may be interested inPhotoelectron spectroscopic study of the E⊗e Jahn-Teller effect in the presence of a tunable spin-orbit interaction. I. Photoionization dynamics of methyl iodide and rotational fine structure of CH3I+ and CD3I+ J. Chem. Phys. 134, 054308 (2011) Photoionization can generate a non-stationary electronic state, which leads to coupled electronnuclear dynamics in molecules. In this article, we choose benzene cation as a prototype because vertical ionization of the neutral species le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 35 publications
7
46
0
Order By: Relevance
“…Previous theoretical studies have shown the system dependence of the effect of nuclear motion using the Ehrenfest method. 8,10,11 Our studies on para-xylene 12 and phenylamines 13 showed that the electron dynamics was not destroyed by the nuclear motion over the studied timeframe (∼20 fs) but the frequency and amplitude was altered, in agreement with studies on methyl substituted benzenes. 11 Only recently has the nuclear delocalization been taken into account in theoretical studies, [12][13][14] where it has been demonstrated that it, in general, will lead to a loss in electron density oscillations, with the time scale being system dependent.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous theoretical studies have shown the system dependence of the effect of nuclear motion using the Ehrenfest method. 8,10,11 Our studies on para-xylene 12 and phenylamines 13 showed that the electron dynamics was not destroyed by the nuclear motion over the studied timeframe (∼20 fs) but the frequency and amplitude was altered, in agreement with studies on methyl substituted benzenes. 11 Only recently has the nuclear delocalization been taken into account in theoretical studies, [12][13][14] where it has been demonstrated that it, in general, will lead to a loss in electron density oscillations, with the time scale being system dependent.…”
Section: Introductionsupporting
confidence: 70%
“…In previous work, [8][9][10][11] we have shown that we can engineer electron dynamics near a conical intersection. However, we have also demonstrated that nuclear spatial delocalization, due to the zero-point energy of the neutral species, can "wash out" the electron density oscillations [12][13][14] because of the spread of the energy gaps in the nuclear wavepacket.…”
Section: Introductionmentioning
confidence: 99%
“…2). In both 040502-2 molecules, the equilibrium geometry of the neutral species is in the vicinity of a crossing between the two lowest-energy electronic states of the cationic species [30,[33][34][35]. The nonzero energy gap at the equilibrium geometry of the neutral species is needed to induce the electron dynamics we study.…”
mentioning
confidence: 99%
“…These simulations predict long-lived oscillating motion in the electronic density at a well-defined frequency, but they neglect both the spatial delocalization of the nuclear wave packet and the nuclear motion. We have previously shown examples of how nuclear motion affects electron dynamics after a few femtoseconds [28][29][30]. Despré and coworkers recently simulated hole migration at a small number * mike.robb@imperial.ac.uk of distorted geometries [31].…”
mentioning
confidence: 99%
“…For example, in studies using Ehrenfest trajectories on the ionisation in aromatic molecules, a distortion from the equilibrium geometry was required to see charge migration in benzene, but it happens spontaneously in toluene and para-xylene [45], as it does in the non-aromatic bismethylene-adamantane [46]. "…”
Section: Model Hamiltonianmentioning
confidence: 99%